Impact of laser-induced pore expansion on thermal emission of porous carbon: of porous carbon. (2017) - Zelenska, Kateryna; Zelensky, Serge; Kopyshinsky, Alexander; Aoki, Toru
Abstract: Irradiation of light-absorbing porous carbon by pulses of a Q-switched YAG:Nd 3+ laser ( λ = 1064 nm, τ = 20 ns, power density of 3-30 MW/cm 2 ) leads to its heating up to temperatures of several thousands of Kelvin which results in pore expansion in the undersurface region and is accompanied by thermal emission. The effect of laser-induced pore expansion on thermal emission (a.k.a. laser-induced incandescence, LII) with an increase in laser irradiation dose was studied. The experimental results and calculation data demonstrate a significant impact of undersurface pore expansion and carbon evaporation on the LII behavior.